The foundation for a joint fire support capability using the NATO model - Adrian MIREA (Bulletin of "Carol I" National Defense University)
Providing joint fire support is an indispensable capability for joint forces that facilitates the achievement of set objectives in all types of operations. Starting from the idea that the development of a fire support doctrine, currently non-existent at the national level, is not sufficient to achieve this capability at the joint force level, I have argued in this paper, other changes that I consider necessary using the NATO capability development model, described by the acronym DOTMLPF-I. In the first part of the article, I have briefly presented the components of the NATO model and then, in the second part, I address the fire support capability as a whole, in terms of doctrine, force structure organization, training, the need to review the available resources, the training of military leaders and fire support personnel, the existing infrastructure and the level of interoperability required to make this capability truly available to the armed forces structures. The actions identified in the eight strands of the NATO model can provide a perspective for developing or enhancing the capability to provide nationally-led joint fire support.